Scripture wars: Justin Martyr's battle to save the Old Testament for Christians - Bennett, Rod (Sophia Institute Press, 2019)
"Recounts conflicts among the early Christians as they sought to determine the proper relation between the God and themes of the Jewish Old Testament and of the Christian New Testament"--